1999
DOI: 10.1016/s0194-5998(99)70238-x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatases 1 and 2A Maintain Endothelial Cells in a Resting State, Limiting the Motility that is Needed for the Morphogenic Process of Angiogenesis

Abstract: Angiogenesis that is induced by cancers, including those of the head and neck, requires endothelial cells to shift from a nonmotile resting state to an increased level of motility. Using a human microvascular endothelial cell line, this study shows the importance of the serine/threonine protein phosphatases 1 (PP1) and 2A (PP2A) in restricting endothelial cell motility. Treatment of endothelial cells with increasing concentrations of the PP1 and PP2A inhibitor okadaic acid resulted in cell rounding and increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 19 publications
(46 reference statements)
1
30
1
Order By: Relevance
“…Whereas a role for PP2A in the regulation of cell motility has been suggested by pharmacological approaches using okadaic acid in transformed cells (90) and cancer cell lines (38,40,91,92), the investigations reported here demonstrate that intracellular PP2A activity can be manipulated in keratinocytes by a novel, receptor-mediated mechanism with resultant effects on the migratory ability of the cells. Our findings open up the possibility of exploring the use of ␤ 2 -adrenergic agonists as pharmaceutical agents to inhibit cell migration.…”
Section: Discussionmentioning
confidence: 50%
“…Whereas a role for PP2A in the regulation of cell motility has been suggested by pharmacological approaches using okadaic acid in transformed cells (90) and cancer cell lines (38,40,91,92), the investigations reported here demonstrate that intracellular PP2A activity can be manipulated in keratinocytes by a novel, receptor-mediated mechanism with resultant effects on the migratory ability of the cells. Our findings open up the possibility of exploring the use of ␤ 2 -adrenergic agonists as pharmaceutical agents to inhibit cell migration.…”
Section: Discussionmentioning
confidence: 50%
“…33 We had also shown increased migration by endothelial cells whose PP-2A is diminished in response to tumor-derived angiogenic factors or whose PP-2A activity is inhibited pharmacologically. 34,25 In identifying the mechanisms by which the decline in PP-2A stimulates tumor migration, our studies showed paxillin serine hyperphosphorylation and tyrosine dephosphorylation, and dissolution of the FAK/Src/paxillin complexes that are important in stabilizing cellular adhesions. Accompanying this dissolution of FAK/Src/paxillin complexes was a reduction in phosphorylation of the inhibitory Y527 residue of Src, suggesting increased Src activity.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, endostatin has been reported to activate the serine/threonine phosphatase PP2A, and this, in turn, perturbs the phosphorylation of endothelial nitric-oxide synthase that is essential for endothelial cell migration and survival (31). Moreover, pharmacological inhibition of protein phosphatase activity has been reported to stimulate the motility of endothelial cells and nonmetastatic tumor cells (32,33). Recently, DEP1/CD148, a membrane-associated tyrosine phosphatase that is up-regulated by confluence and is located at intercellular junctions, has been reported to play a crucial role in developmental vascular organization through the regulation of endothelial proliferation and endothelium-pericyte interactions (34).…”
Section: Discussionmentioning
confidence: 99%